Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.7164/antibiotics.51.1004
|View full text |Cite
|
Sign up to set email alerts
|

New Brominated and Halogen-less Derivatives and Structure-activity Relationship of Azaphilones Inhibiting gp120-CD4 Binding.

Abstract: Novel brominated and halogen-less azaphilone (oxoisochromane) derivatives, 5-bromoochrephilone and dechloroisochromophilone IV, and known derivatives, dechloroisochromophilone III and isorotiorin, were isolated from the culture broth of a producing organism of isochromophilones I and II (azaphilones inhibiting gp120-CD4 binding), Penicillium multicolor FO-2338, fermented in a medium containing potassium bromide. Nineteen azaphilone-related compounds isolated from the above strain and from other fungi were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 16 publications
2
70
0
Order By: Relevance
“…2,3) Although previous publications showed that azaphilones exhibit broad activities in many biological systems, such as cholesteryl ester transfer protein, 4) monoamine oxidase inhibition, 5) endothelin receptor binding, 6) the inhibition of gp120-CD4 binding, 7) telomerase inhibition, 8) the induction of Epstein-Barr virus, 9) and antimicrobial activities, 3,10,11) there is no report about the inhibition of nitric oxide (NO) production by azaphilones.…”
mentioning
confidence: 99%
“…2,3) Although previous publications showed that azaphilones exhibit broad activities in many biological systems, such as cholesteryl ester transfer protein, 4) monoamine oxidase inhibition, 5) endothelin receptor binding, 6) the inhibition of gp120-CD4 binding, 7) telomerase inhibition, 8) the induction of Epstein-Barr virus, 9) and antimicrobial activities, 3,10,11) there is no report about the inhibition of nitric oxide (NO) production by azaphilones.…”
mentioning
confidence: 99%
“…1), which belong to the azaphilones class, from the culture broth of this fungal strain. Azaphilones have various bioactivities such as antimicrobial activity, nitric oxide inhibition (cohaerins) [5], gp120-CD4 binding inhibition (isochromophiliones, ochrephilone, screotiorin and rubrorotiorin) [6], monoamine oxidase inhibition (luteusins, TL-1, TL-2 and chaetoviridins) [7,8] and platelet-derived growth factor binding inhibition (RP1551s) [9]. The metabolites isolated in this investigation exhibited significant cytotoxic activity against the murine P388 leukemia cell line and the human HL-60 leukemia cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The HSQC-TOCSY data listed in Table 1 Table 1. Previously reported 5-alkenylresorcinols usually have isolated double bond(s) in the chain portion of the molecule [1,2,5]. Conjugated double bonds in the chain moiety for resorcinols are unusual.…”
mentioning
confidence: 99%